2024
DOI: 10.3390/s24030831
|View full text |Cite
|
Sign up to set email alerts
|

Classification of the Pathological Range of Motion in Low Back Pain Using Wearable Sensors and Machine Learning

Fernando Villalba-Meneses,
Cesar Guevara,
Alejandro B. Lojan
et al.

Abstract: Low back pain (LBP) is a highly common musculoskeletal condition and the leading cause of work absenteeism. This project aims to develop a medical test to help healthcare professionals decide on and assign physical treatment for patients with nonspecific LBP. The design uses machine learning (ML) models based on the classification of motion capture (MoCap) data obtained from the range of motion (ROM) exercises among healthy and clinically diagnosed patients with LBP from Imbabura–Ecuador. The following seven M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…For instance, it has been reported that the prediction of factors helps improve the prognosis of ACL reconstruction using ML models such as ElasticNet and SVM [26]. Villalba-Meneses et al described the classification using ML models such as SVM of motion capture data obtained from the range of motion exercises among healthy and clinically diagnosed patients with low back pain [27]. Kusunose et al indicated that the integration of MediaPipe with ML models using liner regression and LightGBM for posture analysis has improved accuracy in assessing shoulder abduction angles [20].…”
Section: Figure 15: Conversion From Rotational Displacement Coordinat...mentioning
confidence: 99%
“…For instance, it has been reported that the prediction of factors helps improve the prognosis of ACL reconstruction using ML models such as ElasticNet and SVM [26]. Villalba-Meneses et al described the classification using ML models such as SVM of motion capture data obtained from the range of motion exercises among healthy and clinically diagnosed patients with low back pain [27]. Kusunose et al indicated that the integration of MediaPipe with ML models using liner regression and LightGBM for posture analysis has improved accuracy in assessing shoulder abduction angles [20].…”
Section: Figure 15: Conversion From Rotational Displacement Coordinat...mentioning
confidence: 99%